#### Answer

10y - 23

#### Work Step by Step

5(2y-3) - 8 =
(5 $\times$ 2y) + (5 $\times$ -3) -8 =
10y - 15 - 8 =
10y - 23

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

10y - 23

5(2y-3) - 8 =
(5 $\times$ 2y) + (5 $\times$ -3) -8 =
10y - 15 - 8 =
10y - 23

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.